THE CONCEPTUALIZATION OF BANJARESE CULTURE THROUGH ADJECTIVES IN BANJARESE LULLABIES - Jumainah Jumainah; Agustina Lestary; Ninuk Krismanti (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
The focus of this study is to conceptualize Banjarese living values through the investigation of adjectives used in Banjarese lullabies. Singing lullabies while rocking the baby is a common practice for Banjarese people. The lullabies becoming the subject of the study of this research are the ones with Banjarese lyrics. In practice, Banjarese parents do not only sing lullabies in their tribe language but also in either Arabic or Indonesian. The data are collected through three techniques: observation, interview, and documentation. The data are obtained from five regions all over South Kalimantan to represent both Banjar Hulu and Banjar Kuala. The adjectives found the lullabies being investigated are analyzed using Cultural Linguistic approach. The results of the study show a close connection between adjectives used in the lullabies and beliefs of Banjarese people. Adjectives describing desired and undesired traits of children reflect Islamic teachings.